The role of nutrition, intimate partner violence and social support in prenatal depressive symptoms in rural Ethiopia: community based birth cohort study. - Woldetensay, Yitbarek Kidane.; Belachew, Tefera.; Biesalski, Hans Konrad.; Ghosh, Shibani.; Lacruz, Maria Elena.; Scherbaum, Veronika.; Kantelhardt, Eva Johanna. (2018)
Background: Depression during pregnancy has far-reaching adverse consequences on mothers, children and the whole family. The magnitude and determinants of prenatal depressive symptoms in low-resource countries are not well established. This study aims to describe the prevalence of prenatal depressive symptoms and whether it is associated with maternal nutrition, intimate partner violence and social support among pregnant women in rural Ethiopia.; Keywords: Prenatal depression, Household food insecurity, Anaemia, Intimate partner violence, Social support, PHQ-9, Ethiopia.; Springer Open.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy